Citrus medica essential oil exhibits significant antimicrobial and antiproliferative activity. (October 2017) - Mitropoulou, Gregoria; Fitsiou, Eleni; Spyridopoulou, Katerina; Tiptiri-Kourpeti, Angeliki; Bardouki, Haido; Vamvakias, Manolis; Panas, Panayiotis; Chlichlia, Katerina; Pappa, Aglaia; Kourkoutas, Yiannis
Abstract: The aim of the study was to investigate the antimicrobial and antiproliferative activity of Citrus medica essential oil produced by hydrostillation and evaluate its commercial potential in the food industry. The main constituent of the C. medica peels and essential oil identified by SPME GC/MS or GC/MS analysis was limonene (≈88 and 64%, respectively). The antimicrobial properties were assayed and the minimum inhibitory and non-inhibitory concentration values were determined. Both C. medica essential oil and limonene were effective against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Listeria monocytogenes, Salmonella Enteritidis, Salmonella Typhimurium, Pseudomonas fragi, Saccharomyces cerevisiae and Aspergillus niger . MIC and MBC values for the oil ranged 845 ± 26–2008 ± 43 mg/l and 4184–8368 mg/l, respectively. C. medica essential oil was further assessed in different human cancer cell lines (HepG2, Caco2, MCF-7, and THP-1) and was found to have significant antiproliferative activity, being the most effective against the Caco2 cells. Citrus medica oil and limonene were shown to possess cancer-specific activity when tested against the skin melanoma A375 cells and normal skin cells (HaCat). The oil also appeared to inhibit LPS-induced nitric oxide (NO) production in RAW 264.7 cells. Highlights: The biological properties of Citrus medica essential oil were studied. The main constituent of C. medica peels and essential oil was limonene. The essential oil was effective against spoilage and pathogenic microbes. The essential oil was found to have significant antiproliferative activity. The oil appeared to inhibit LPS-induced nitric oxide production in RAW 264.7 cells.